Wanderings for Spain of a “inquirer to the modern one of northern race” - Henningsen, Gustav (Huarte de San Juan. Geografía e Historia, 2010)
The author traces his intellectual autobiography from when he was a student in his native country, Denmark. His first steps in research focused on folklore of the Nordic countries, and this led him to undertake fieldwork on sailors’ folk yarns. During an interview on a southern Danish island, by coincidence he discovered that the local population still believed in witches. This was the starting point for his PhD thesis which gradually took shape as he carried out research in Spain (Galicia, the Basque Country and Navarre). The discovery of documents regarding the inquisitor Salazar Frías in the National Historical Archive led him to focus his studies on the Inquisition and the famous witch trial of Zugarramurdi by the Court of Logroño in the early seventeenth century.